Corporate investments for public land management: insights into the Forest Service's corporate partnerships - Collins, Natasha, author; Schultz, Courtney, advisor; Jones, Kelly, committee member; Huber-Stearns, Heidi, committee member (Colorado State University. Libraries, 2020)
There is a shift in environmental governance towards devolution and neoliberalism, whereby federal land management agencies increasingly rely on external actors to help them meet their management objectives. For the U.S. Forest Service, budget deficiencies and increasingly complex management challenges, in part due to climate change, drive the agency to seek external funding sources, including for-profit companies. As reliance on companies to meet gaps in agency funding and capacity increases, there is a need to better understand the expectations and interests of these corporate partners. My thesis aims to better understand the Forest Service’s corporate partners by identifying key partners and their mechanisms for investment, corporate motivations for engagement, company interests in metrics and return on investment, and overall successes and challenges of the partnerships. To address these research questions I conducted interviews with Forest Service staff, both in the Washington Office and with Regional partnership coordinators, for-profit companies funding projects on national forests related to climate change, and key non-profit organizations that serve as intermediaries between the Forest Service and companies to channel funds and implement the work. In the following thesis I synthesize my findings into two stand-alone chapters, bookended by an introduction and conclusion chapter. The first chapter is a comprehensive report to the Forest Service Office of Sustainability and Climate, which funded this project, regarding the mechanisms, motivations, desired metrics and overall successes and challenges of corporate partnerships with the Forest Service. Among other things, I find that corporate partners have a iii limited understanding of what national forests are, the role the Forest Service plays as an agency, and avenues that exist for partnerships with the Forest Service. I offer a few recommendations for the agency moving forward, including, improved storytelling by the Forest Service to corporate partners regarding who the agency is and the benefits of partnership, increased collaboration between companies to help tackle projects of larger scale, standardized metrics for improved measurement of project outcomes, and further developed options to participate in carbon markets on national forests. The second chapter is intended for submission to a peer-reviewed journal. The article dives deeper into exploring corporate motivations for engagement in these types of projects. I find that companies engage in projects for a variety of reasons, primarily including: desires to achieve sustainability goals driven by leadership; stakeholder pressures, such as those from consumers, employees, and investors; company characteristics, including the dependency of a company’s products or services relying on benefits that forests provide; and marketing tied to a company’s brand or reputation. Overall, insight into this topic can inform the Forest Service on its private partners in order to improve and expand these types of partnerships moving forward. This research also contributes to literature regarding the increasing role of public-private partnerships, consistent with a broader shift towards neoliberal approaches in environmental governance whereby private actors contribute funding and capacity in ways that help the Forest Service manage public forests, but also significantly influence public agency activities. Further research is still needed to evaluate the impact of increasing corporate influence on public lands management and to further explore the added value of intermediary organizations for the success of these partnerships.
Keywords: corporate social responsibility; national forests; public-private partnerships; Forest Service; climate change; public land management